Service Quality and Non-Muslim Satisfaction Using Sharia Bank Products and Services - Nova Ch Mamuaya (Shirkah: Journal of Economics and Business, 2017)
Some studies show that religious belief does not take effect affecting consumer using sharia bank products and services. This research has implemented six dimensions of Othman and Owen which modified five dimensions of Parasuraman with adding compliance dimension. The six dimensions of Othman & Owen are known as CARTER (compliance, assurance, reliability, tangible, empathy, and responsiveness). The research purpose is to analyze compliance, assurance, reliability, tangible, empathy, and responsiveness effect on non-Muslim customer satisfaction on sharia bank products and services at Manado Sulawesi Utara partially or simultaneously. The data was gathered with questionnaire instruments of 70 respondents, measured with five Likert scale five dots. The research result shows compliance, assurance, reliability, tangible, empathy, and responsiveness has significant effect on customer satisfaction. Responsive has most strong effect and compliance is the weakest.  Keywords:  Sharia Bank, non-Muslim, quality service, customer satisfaction, Manado